Port Scanning and Its Detection in Physical Network - Pandey, Nitish G.; Thakur, Roshan S. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The networking infrastructure is growing day by day and becoming more complex. With the increase in the networks, the number of attacks on these networks or some hosts in the network also increases. The main concern now-a-days is to provide network security. The attackers carry out various types of malicious activities in order to harm the system or to get some information. One of the techniques is port scanning. The attackers carry out scanning of various ports in order to gain information of about various types of services that are available. The attackers send messages to various ports and waits for an answer. This message helps to get information about various types of services that are present at all the ports. The network administrators also use port scan in order to check the system vulnerabilities. The port scan detection helps to know the IP address of the hosts that are doing the port scan in a network. The detection of these scanning activities thus becomes very important. The detection helps to take the necessary preventive measures after port scanning of the ports on a system is been detected.